Predictive Validity of the MAYSI-2 and PAI-A for Suicide-Related Behavior and Nonsuicidal Self-Injury Among Adjudicated Adolescent Offenders on Probation - Shaffer, Catherine S. (Criminal justice and behavior, 2018)
This prospective study evaluated the ability of the MAYSI-2 and PAI-A to predict suicide-related behavior (SRB) and nonsuicidal self-injury (NSSI) among adjudicated adolescent offenders on probation. Predictive validity of the MAYSI-2 for SRB and NSSI has generally been postdictively examined among detained adolescents. In addition, no published studies have examined the predictive validity of the PAI-A for SRB and NSSI among adolescent offenders. Neither the MAYSI-2 nor PAI-A added incremental predictive validity above lifetime SRB or NSSI. However, several MAYSI-2 and PAI-A subscales were predictive of SRB or NSSI. With some exceptions, most recommended instrument cut-off scores differentiated between low-risk and high-risk youth. These findings suggest that the MAYSI-2 and PAI-A hold promise for evaluating SRB and NSSI among justice-involved youth. In addition, these findings contribute to more informed decisions regarding the use of these tools and can be used to inform SRB and NSSI prevention efforts.